ANALISIS YURIDIS TERHADAP PERBUATAN MELAWAN HUKUM PADA PERJANJIAN KERJASAMA YANG DIBUAT OLEH MUHAMMAD NUZUL SEBAGAI PIHAK DALAM PERJANJIAN (STUDI KASUS TERHADAP PUTUSAN MAHKAMAH AGUNG NOMOR 3198 K/PDT/2010) - Muhammad Tahir Hutasuhut; Maryati Bachtiar Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Issues in Supreme Court Decision No. 3198 K / Pdt / 2010 which decides Muhammad Nuzul has committed an unlawful act for violating Law No. 30 Year 2004 concerning Notary, tort in the form of intervention in the Deed of Cooperation Agreement No. 208 dated January 30, 2006 made by Muhammad Nuzul, where the agreement was made with the tort and the only benefit fraud Muhammad Nuzul, and tort of using the money belongs to the Duma Sari Lubis given to Muhammad Nuzul for capital building stations Kamuyang River Payakumbuh, but the capital he used unlawfully by not clear and there are no reports for accountability for the use of the money. Keywords: Decision, Notary Law, Agreement, act against the rights